A smartphone‐based technology package to support independent activity in people with intellectual disability and blindness. Issue 5 (13th March 2018) - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Chiariello, Valeria; Perilli, Viviana; Campodonico, Francesca
Abstract : The study assessed a technology package, based on commercial devices and designed to promote independent activity engagement, with 6 participants with intellectual disability and blindness. The technology included: (1) a smartphone Samsung Galaxy A3 fitted with Android 6.0 operating system, Bluetooth 4.0, light sensor, and Macrodroid application, (2) portable light sources, and (3) portable Bluetooth speakers. Data showed that the participants' mean percentages of independent activity responses were (virtually) 0 during baseline and increased to above 90 during the intervention when the technology was available.